Selected motivational variables that influence spectator attendance of professional woman's soccer matches. - Mabasa, Peace Nhlawutelo (Vaal University of Technology, 2022)
Sport has become the great unifier globally since governments, countries and organisations are using it as a resource to bring people together. The sport industry is one of the fastest rising business segments and its primary aim/objective is to generate the revenue from sport spectators. In the past decade, the behaviour of sport spectators has received increasing attention in academic literature. A better understanding of how and why sport spectators go to stadiums and travel great distances to support their sport clubs is of great interest to sport marketers. Soccer, in particular, is perhaps one of the greatest sport phenomena in terms of its attraction for hundreds of thousands of occasional spectators of every age and gender, who come together in soccer stadiums around the globe every week to watch games. In South Africa, soccer is the leading sport from both a participation and spectator viewpoint. Understanding sport consumers willingness to attend is arguably one of the most important concerns in sport marketing and consumer-relationship management. As found in sport consumption literature, a “good relationship with sport consumers by sport clubs is an essential factor for a successful sport business” because it is much cheaper to serve satisfied consumers and easier to sustain their support. The purpose of this study was to examine selected motivational variables that influence spectators’ attendance of professional women’s soccer matches to better understand the development of the sports consumption sector. There is an absence of research conducted concerning this direction and subsequently a lack of existing literature, especially among women’s sport. To contribute to filling this void, this study attempts to measure the relationships between these variables. Earlier research has demonstrated that consumers’ willingness to attend is highly determined by their satisfaction. This study is descriptive and correlational in nature and follows a quantitative research approach. The target population comprised spectators of professional women’s soccer in the Gauteng province of South Africa. A snowball sampling technique was used to identify the participants fitting the predetermined sample standards. A total number of 316 questionnaires were received and analysed. Relevant areas, research approaches and data acquiring procedures were described. Additionally, means and factor analysis were performed to determine the level of selected motivational variables, team satisfaction and willingness to attend of spectators and to establish the underlying factors of the constructs respectively. Moreover, a correlation analysis was conducted to establish the strength and direction of the relationship between the study variables. Lastly, a regression analysis was performed to check the predictive relationship between the study’s constructs. The study revealed that motivational variables (vicarious achievement, involvement, social interaction, perceived value) have a significant relationship with spectator satisfaction. In addition, spectator satisfaction was found to be the determinant of spectator willingness to attend professional women’s soccer matches. Based on the results of this study, this research adds to the scant literature on spectators of women’s sport and proposes perspectives on the level of motives and behaviours of spectators, which can be used by women’s sport organisations and government organisations in elevating women’s soccer in South Africa. In this way, sport organisations could develop spectator engagement campaigns and marketing materials in order to engender and enhance women’s spectator participation. Further, sport managers and sport marketers should make every effort to increase the perceived value of services such as fees which are fair, albeit under the global negative economic climate, in order to satisfy the needs of spectators and at the same time reap rewards from the presence of spectators in stadiums and ensure that this presence continues. Based on these findings, limitations as well as future research opportunities and contributions of this study are discussed.
M. Tech. (Department of Business Administration, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Sport consumption; Involvement; Team identification; Vicarious achievement; Perceived value; Satisfaction; Social interaction spectator attendance; Willingness to attend; Dissertations, Academic -- South Africa.; Soccer for women.; Consumer behavior.; Sports -- Marketing.